Exosomal proteins as prognostic biomarkers in non‐small cell lung cancer. Issue 10 (21st October 2016) - Sandfeld-Paulsen, B.; Aggerholm-Pedersen, N.; Bæk, R.; Jakobsen, K.R.; Meldgaard, P.; Folkersen, B.H.; Rasmussen, T.R.; Varming, K.; Jørgensen, M.M.; Sorensen, B.S.
Abstract: Background: Use of exosomes as biomarkers in non‐small cell lung cancer (NSCLC) is an intriguing approach in the liquid‐biopsy era. Exosomes are nano‐sized vesicles with membrane‐bound proteins that reflect their originating cell. Prognostic biomarkers are needed to improve patient selection for optimal treatment. We here evaluate exosomes by protein phenotyping as a prognostic biomarker in NSCLC. Methods: Exosomes from plasma of 276 NSCLC patients were phenotyped using the Extracellular Vesicle Array; 49 antibodies captured the proteins on the exosomes, and a cocktail of biotin‐conjugated antibodies binding the general exosome markers CD9, CD81 and CD63 was used to visualise the captured exosomes. For each individual membrane‐bound protein, results were analysed based on presence, in a concentration‐dependent manner, and correlated to overall survival (OS). Results: The 49 proteins attached to the exosomal membrane were evaluated. NY‐ESO‐1, EGFR, PLAP, EpCam and Alix had a significant concentration‐dependent impact on inferior OS. Due to multiple testing, NY‐ESO‐1 was the only marker that maintained a significant impact on inferior survival (hazard rate (HR) 1.78 95% (1.78–2.44); p = 0.0001) after Bonferroni correction. Results were adjusted for clinico‐pathological characteristics, stage, histology, age, sex and performance status. Conclusion: We illustrate the promising aspects associated with the use of exosomal membrane‐bound proteins as a biomarker and demonstrate that they are a strong prognostic biomarker in NSCLC. Highlights: In NSCLC, exosomal membrane‐bound protein profiling is feasible in liquid biopsies. Nine exosomal proteins showed potential as prognostic markers in NSCLC. Exosomal NY‐ESO‐1 was a strong prognostic biomarkers in NSCLC.